A New UHPLC Analytical Method for St. John’s Wort (Hypericum perforatum) Extracts - Lisa Wang; Afoke Ibi; Chuck Chang; Julia Solnier (Separations, 2023)
Commonly used to treat mood disorders, St. John’s Wort (Hypericum perforatum) is a popular herb in the natural health products industry. The potency of its active ingredients can be determined using a number of different analytical methods, but it is more widely determined using high performance liquid chromatography (HPLC). While monographs in the United States Pharmacopeia (USP) can often be relied upon for suitable analytical methods, the method proposed for determining hypericin content in St. John’s Wort products is inefficient in carrying out this purpose. This paper presents a modified new HPLC method for determining the hypericin content that can also be used for St. John’s Worts capsules and tablets by making use of purified hypericin as a chemical standard instead of oxybenzone, applying a wavelength of 588 nm during analysis and utilizing a binary instead of ternary mobile phase gradient. The resulting method and sample chromatograms provide better resolved, more easily identifiable peaks, shorter run time, and increased sustainability compared to the original USP method. This proposed method was developed using the more refined ultra-high performance liquid chromatography (UHPLC) and serves as a more accurate and reliable method for determining hypericin content in St. John’s Wort.